Oxytocin improves mentalizing – Pronounced effects for individuals with attenuated ability to empathize. (March 2015) - Feeser, Melanie; Fan, Yan; Weigand, Anne; Hahn, Adam; Gärtner, Matti; Böker, Heinz; Grimm, Simone; Bajbouj, Malek
Highlights: A single dose of intranasally administered OXT enhanced mentalizing accuracy using the Reading the Mind in the Eye Test. This effect was only found for difficult items. OXT specifically enhanced mentalizing accuracy in participants with lower empathy scores. We suggest that the effects of OXT strongly depend on baseline social-cognitive skills such as empathy. Summary: The ability to predict the behavior of others based on their mental states is crucial for social functioning. Previous studies have provided evidence for the role of Oxytocin (OXT) in enhancing the ability to mentalize. It has also been demonstrated that the effect of OXT seems to strongly depend on socio-cognitive skills with more pronounced effects in individuals with lower socio-cognitive skills. Although recent studies indicate that mentalizing is related to empathy, no study has yet examined whether the effects of OXT on mentalizing depend on the ability to empathize. 71 male participants participated in a double-blind, between-subjects, placebo-controlled experiment. The Reading the Mind in the Eye Test (RMET) was used to investigate mentalizing abilities. We analyzed the effect of OXT on easy and difficult items of the RMET depending on differential empathy scores of the participants as assessed with the Empathy Quotient (EQ). Our results showed that OXT improves mentalizing for difficult but not for easy items. We generally observed increased mentalizing accuracy in participants with higher empathy scores. Importantly, however, whereas the performance in participants with higher empathy scores was comparable in both OXT and placebo condition, OXT specifically enhanced mentalizing accuracy in participants with lower empathy scores. Our findings suggest that OXT enhances mentalizing abilities. However, we also demonstrate that not all participants benefited from OXT application. It seems that the effects of OXT strongly depend on baseline social-cognitive skills such as empathy.